The motivation of muzakki to pay zakat on income: study at Tabung Haji Kuching / Siti Khatijah Yusuf - Yusuf, Siti Khatijah (Faculty of Business Management, 2018)
Zakat is a part of the pillar of Islam or specifically it is placed at third pillar of Islam which Muslim is obliged to pay zakat especially the one who are meet the requirement to pay zakat. Allah S WT obliged His servant to fulfil their responsibility as Muslim. Zakat can lead to a better socio-economic towards state and country which will help Muslim community to develop their quality of life. The purpose of this study to investigate the factors that motivate Muzakki to pay Zakat on Income with the target respondent at Tabung Haji Kuching. The research design for this study will employ quantitative method of random sampling and survey questionnaires that have been developed based on a through and detailed analysis of the relevant literature. There are four variables to study the relationship that can motivate Muzakki to pay Zakat on Income. A total of 100 respondent have been answer the questionnaire given with the result that all of them are almost accurate with the hypotheses. This study implies that in order Muzakki to pay their zakat at Tabung Baitulmal, Islamic cultures and custom should be preserved or practiced among Muslim in Malaysia especially in Sarawak, government should enhance regulation pertaining zakat management purely and the people of Sarawak especially need to be equipped with the relevant knowledge on the obligation of zakat payment.